1992
DOI: 10.1037/0022-3514.62.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting effects of reciprocation wariness on interpersonal relationships.

Abstract: Students with high reciprocation wariness, a general fear of exploitation in interpersonal relationships, showed (a) a markedly reduced positive response to cooperative communication in a Prisoner's Dilemma bargaining task, (b) a greater negative response to uncooperative communication, and (c) an increased positive response to the prospect of long-term interaction. Friends and roommates of high-wary students evaluated them as unsympathetic, inconsiderate, and manipulative. Students who were supervised by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 69 publications
12
111
0
1
Order By: Relevance
“…Tukey's q-test revealed that UNCO-OPERATIVE discussion lowered SIT in comparison with COOPERATIVE or NEUTRAL discussion. These results agree with those obtained by Lindskold, Betz, and Walters (1986), Lindskold, Han, and Betz (1986), Tedeschi et al (1980), andCotterell et al (1992). Number of cooperators in the first trial.…”
Section: Resultssupporting
confidence: 83%
“…Tukey's q-test revealed that UNCO-OPERATIVE discussion lowered SIT in comparison with COOPERATIVE or NEUTRAL discussion. These results agree with those obtained by Lindskold, Betz, and Walters (1986), Lindskold, Han, and Betz (1986), Tedeschi et al (1980), andCotterell et al (1992). Number of cooperators in the first trial.…”
Section: Resultssupporting
confidence: 83%
“…In our investigation, we focused on the initial and spontaneous reactions and behaviors people display in a dyadic setting as a consequence of their achievement goals and the performance feedback that they receive. It may be assumed that the behaviors displayed by the participants directly reflected considerations that were evoked by their goal focus (Cotterell, Eisenberger, & Speicher, 1992). Further field research needs to be conducted to investigate whether the present findings have external validity.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Beliefs in the efficacy and widespread use of reciprocity-based behaviours and expectations of others' reciprocal behaviour certainly play an important role in predicting reciprocating behaviours (see e.g. Cotterell, Eisenberger, & Speicher, 1992). However, these beliefs should be conceptually distinguished from the actual performance of a reciprocal behaviour.…”
Section: Individual Differences In Reciprocitymentioning
confidence: 99%